A trust-based method for mitigating cache poisoning in Name Data Networking. (15th February 2018) - Rezaeifar, Zeinab; Wang, Jian; Oh, Heekuck
Abstract: Mitigating Cache poisoning in Name Data Networking (NDN) can significantly improve the effect of ubiquitous data caching, which is a prominent feature in NDN. However, since verification signatures cannot be practical in the network routers, finding a suitable method to mitigate cache poisoning in NDN routers is a challenge. Therefore, in this paper, the proposed method tries to identify invalid contents by the defined parameters: popularity, negative feedback and credibility. Then, with combining these three metrics, the trust model is presented to estimate the validity of each content. Moreover, the proposed method creates an incentive among users to exchange trusted contents. Finally, the evaluation results indicate the effectiveness of the proposed method to detect invalid contents as compared to previous methods.